2020
DOI: 10.1177/1077801220905663
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Incoming Male College Students’ Proclivity to Perpetrate Sexual Assault

Abstract: This study examined incoming male college students’ proclivity to perpetrate sexual assault at a large public university in the Northeast ( n = 1,619). Overall, self-reported proclivity to perpetrate was low (between 20–26%). Students’ perception that a peer would intervene as a bystander was negatively associated with proclivity, while acceptance of certain rape myths was positively associated with proclivity. Students who intended to join a fraternity and White students had increased proclivity to perpetrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 92 publications
(119 reference statements)
0
7
0
Order By: Relevance
“…Demographic Variables : Ostensibly, there were demographic similarities between SAs and NSAs, and univariate analyses showed that participants could only be differentiated by their ethnicity, p = .048 (see Supplementary Table S2 for post hoc pairwise comparisons). Given recent contentions that ethnicity may explain sexual aggression through social or cultural norms (see Palmer et al, 2020 ), we decided to include this variable in our logistic regression model.…”
Section: Resultsmentioning
confidence: 99%
“…Demographic Variables : Ostensibly, there were demographic similarities between SAs and NSAs, and univariate analyses showed that participants could only be differentiated by their ethnicity, p = .048 (see Supplementary Table S2 for post hoc pairwise comparisons). Given recent contentions that ethnicity may explain sexual aggression through social or cultural norms (see Palmer et al, 2020 ), we decided to include this variable in our logistic regression model.…”
Section: Resultsmentioning
confidence: 99%
“…While there have been relatively few assessments of sexual aggression perpetration on university campuses, climate survey data have shown that male students commit the majority of offences (Anderson et al, 2021 ; Jones et al, 2020 ). This finding has been validated across several large-scale studies with male students, where approximately one-in-four report a history of sexual perpetration (Anderson et al, 2021 ) and notably more report a proclivity towards harmful sexual activity (e.g., Palmer et al, 2021 ; Wong et al, 2020 ; Zounlome & Wong, 2019 )—a strong indicator of future campus-based sexual offending (e.g., Malamuth et al, 1995 ; Zounlome & Wong, 2019 ). Worryingly, despite recent federal guidelines to make campuses safer, self-reported perpetration rates among male US student samples have increased over the past three decades (Koss et al, 2022 ).…”
Section: Introductionmentioning
confidence: 58%
“…Both RMA and rape proclivity have been used as outcomes in rape programs to demonstrate effects of program participation (Anderson & Whiston, 2005; DeGue et al, 2014; De La Rue, Polanin, Espelage, & Pigott, 2014). Several studies have demonstrated an association between RMA and rape proclivity (Bohner, Pina, Viki, & Siebler, 2010; Bohner et al, 2006; Chapleau & Oswald, 2010; Palmer, McMahon, & Fissel, 2020; Süssenbach, Bohner, & Eyssel, 2013). Scholars have hypothesized that rape myths may act as “psychological neutralizers” which allow men to disregard their usual inhibitions against perpetuating sexual violence, increasing their rape proclivity by rationalizing it (Bohner et al, 1998; Burt, 1980).…”
Section: Beliefs Associated With Sexual Violence Perpetration: Rma An...mentioning
confidence: 99%